A Study To Assess Effect Of Probiotics On The Amount And Ph Of Saliva In Edentulous Patients (Journal of Pharmaceutical Negative Results, 2023)
IntroductionSurvival rate and its effect on the atraumatic restorative treatment are essential. In this situation, the detrimental impact plays a vital role in salivary flow. It helps for reducing stomatitis's insignificant number. According to some reports, probiotics have been shown to increase saliva production in the oral cavity. Therefore, this motive aimed to measure the volume and pH of saliva in patients with complete dentition after taking probiotics for 60 days.MethodsSpecific materials and methods are needed to identify so that study can be completed without any challenges. Probiotic capsules can be used in this situation as a saliva collection kit. After that, probiotic pills containing 3.3 107 CFU/g were given to each patient to take once daily for 60 days. Patients' saliva was born, its quantity and pH were calculated, and its results were compared to the initial value.ResultsMoreover, Table 2 exhibits the frequency distribution "before and after 60 days in terms of whole stimulated and unstimulated pH and saliva".ConclusionHowever, the precise molecular mechanism behind this action is still unknown, and further research is required on a larger scale to understand it. The average unstimulated and stimulated saliva enhanced from base to that after sixty days when saliva samples were compared, with the differences being 0.406 and 0.433, respectively.